Kulturisasi Ritual Tolak Bala pada Masyarakat Desa Tanjung Jariangau - Siti Amaliah; Muslimah Muslimah; Muhammad Redha Anshari (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study explores the tolak bala ritual that continues to be preserved by the people of Tanjung Jariangau Village. The ritual is a cultural heritage passed down from ancestors and remains significant even in today’s modern era. The tolak bala ritual is usually performed during outbreaks, natural disasters, or other calamities, aiming to ward off misfortunes and restore harmony within the community. The practice involves reciting specific prayers, such as salawat, and carrying out collective traditional ceremonies that engage the wider community. Interestingly, although the entire population is Muslim, the ritual reflects a form of religious syncretism that combines Islamic values with elements of Hinduism, Buddhism, animism, and dynamism. This illustrates how local traditions adapt and coexist with the religious beliefs of the community. The purpose of this study is to examine the meaning and implementation of the tolak bala ritual and to highlight the integration of Islamic teachings within the tradition. The findings reveal that the ritual is not only regarded as a means of protecting individuals, families, and the village from disaster, but also serves as a form of communal healing and a medium to strengthen social cohesion. Therefore, tolak bala serves a dual function, both religious and social. In conclusion, the ritual reflects a harmonious integration of local cultural traditions with religious values and represents a living cultural identity that is continuously maintained by the people of Tanjung Jariangau. Keywords: Ritual, Tolak Bala, Syncretism